A Local Update and Refinement method of the Global Terrain Nature Grid. Issue 3 (February 2019) - Wang, Hongbin; Zhao, Junwu; Liu, Yuanlin; Ma, Jiayi
Abstract: As an important data model for the exploration and interpretation of large range natural phenomena such as hydrological analysis, climatic analysis, simulation of sea level rise, Global Terrain Nature Grid (GTNG) partitions the earth surface into nature cells based on Morse complex, directly revealing the required global terrain morphological information at different scales. Recently, with the development of data acquisition technology, high temporal/spatial resolution terrain data sets are being collected. However, there is no top-down local refinement operation for GTNG, which is very important to the representation of Morse features dealing with the ever-growing global massive terrain data. On the other hand, due to the updating of local terrain data, GTNG needs a corresponding local reconstruction method to suit the present situation. To this aim, an accurate and efficient method to update and refine GTNG locally is presented. First, local terrain is updated through constraint Delaunay triangulation. Then, local cells of GTNG are computed and updated according to the topological relation between the terrain triangles and Morse cells. By this method, local cells of GTNG can not only be updated but also be refined successively using terrain data with higher resolution than the underlying mesh. In the end, an experiment is done to validate the correctness and feasibility of this method.